362 Rare presentation of adnexal mass: follicular dendritic cell sarcoma, a case report. (18th September 2019) - Sartorelli, V; Fabiane de Andrade Ferreira Larre, A; Camargo Guimarães Forghieri, M; Leitão, L; Borges de Souza, L; Rezende Dias, AL; Lopes, A; Lowndes de Souza Pinto, G; Lucio Rangel Costa, R
Abstract : Objectives: To report a rare histopathological diagnosis of adnexal mass. Methods: We describe a case of a patient referred to our Gynecology Oncology service to investigate an adnexal mass found in routine exams. Results: A 58-year-old woman was referred to our service due to an adnexal mass associated with hypogastric pain. Physical examination revealed a hardened mass bulging the anterior-right vaginal wall, discreetly painful by the touch. A magnetic resonance imaging (MRI) of the pelvis revealed a right adnexal heterogeneous mass measuring 9, 5 x 4, 5 x 6, 5 cm adjacent to the iliac vessels. There were no altered tumoral markers. She underwent to exploratory laparotomy, and a mass in the right broad ligament was found. Bilateral salpingoophorectomy and total hysterectomy was performed, as well as the excision of the tumor (wich was adhered to the right iliac vein, pelvic wall and obturator fossa) and homolateral pelvic lymphadenectomy. The intraoperatory pathologic evaluation of the lesion suggested a Carcinoma. The anatomopathologycal study of the retroperitoneal tumor was consistent with poorly differentiated malignant neoplasm. The immunohistochemical analysis showed a strong and diffuse expression of CD23 and negative expression of other markers, ruling out the previous diagnosis and bringing to light the actual histology of the tumor, follicular dendritic cell sarcoma (FDCS). Conclusions: It is known that FDCS is an uncommon lymphoid neoplasm, especially in pelvic location, with low incidence and indolent growth, difficult to diagnose, but with high rates of local recurrence and eventually distant metastases. There is no standard treatment established and adjuvant therapy is still controversial.